Water Resource Vulnerability Assessment of Changchun City Based on DPSIR-TOPSIS Model - Zhu Yifan; He Hong; Zhang Wenjing; Du Shanghai (Shuitu baochi tongbao)
[Objective] The current situation and influencing factors of water resource vulnerability in Changchun City, Jilin Province were analyzed in order to provide a reference for the development, utilization, protection, and management of water resources in Changchun City. [Methods] The DPSIR model was used to construct a water resource vulnerability evaluation system based on 19 indicators. The entropy weighting method was used to calculate the weights of each indicator. The TOPSIS method was used to evaluate the water resources vulnerability status of Changchun City from 2005 to 2019. [Results] The water resource system of Changchun City was at a mild vulnerability level in 2005, and fluctuated between 0.3 and 0.5 from 2006 to 2019 (a medium vulnerability level). The influence of each sub-system on the comprehensive evaluation results followed the order of pressure (P) > impact (I) > driving force (D) > state (S) > response (R). [Conclusion] Total water use and total water resources are important factors influencing water resource vulnerability in Changchun City, and groundwater has a greater impact on water resource vulnerability than surface water. The government should continue to increase investments in energy conservation and environmental protection, introduce relevant environmental protection policies, improve the treatment of urban water pollution, further optimize the allocation of water resources, promote water-saving irrigation technology, improve the utilization rate of water resources, and alleviate the pressure on water supplies in dry years.